Study of filtration diluted crude palm oil slurry using labscale pressure filter - Mustapha, Sa'ari; Saidi, Hamdani (Jawatankuasa Penyelidikan & Perundingan, Fakulti Kej. Kimia & Kej. Sumber Asli, UTM, 1993)
A labscale pressure filter has beer, developed to study the filtration behaviour of diluted crude palm oil slurry. The apparatus mainly consists of two parts viz. a mixer and a filter which are placed in a oven for controlling operating temperature. The system is connected to a data acquisition system for recording data of applied pressure, medium pressure, filter temperature, weight of filtrate and mixer speed in a spread sheet. Filtration of DCPOS was carried out at a temperature range 60C – 90C and applied pressure 1 bar - 4 bar using a polyester multifilament woven cloth as filter medium. The results have shown that the filter System Was fully capable and suitable to be used to study filtration behaviour of DCPOS. The optimum process condition to give he highest filtration rate was at 2 bar and 90C. The effect of pressure and temperature to the filtrate flowrate and cake compressibility were also discussed.